Discrimination at the Workplace - Findings from the European Working Condition Survey : Types of Discrimination Practices and their Characteristics - Grabowska, Izabela; Węziak-Białowolska, Dorota (Dyskryminacja w miejscu pracy na podstawie Europejskiego Badania Warunków Pracy - rodzaje praktyk dyskryminacyjnych i ich charakterystyka, 2011)
The aim of this article is to analyze discrimination at the workplace in the EU. Data used in the analysis comes from the European Working Conditions Survey. Since we assume that discrimination is a latent and discrete phenomenon, in order to classify respondents the latent class analysis is employed. The analysis performed enables to define six distinct groups of employees according to the feeling of being discriminated at the workplace. The general findings are as follows: we recognize types of discriminatory practices that are present in the labour market, we show which discriminatory practices coexist there, we discover that some types of discriminatory practices in the presence of others become more important and some become less important.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 194, s. 202-216
Keywords: dyskryminacja w zatrudnieniu; praca; rynek pracy; employment discrimination; labour; labour market